Case Report: Pediatric AML with TBC1D15::RAB21 fusion and FLT3-ITD/NPM1 co-mutation: diagnostic pitfalls in morphologic mimicry of acute promyelocytic leukemia - Yao, Qiang; Chen, Xiaoyong; Luo, Meizhu; Lin, Zhenhu; Fu, Xiaoying (Frontiers in Oncology, 2026)
We report a diagnostically challenging case of acute myeloid leukemia (AML) in a 2-year-9-month-old boy, presenting with diarrhea and pancytopenia. Bone marrow aspiration revealed 90% blasts exhibiting cup-like nuclei and azurophilic granules, morphologically mimicking acute promyelocytic leukemia (APL).However, immunophenotyping was inconsistent with classic APL, showing positivity for CD33 and cytoplasmic myeloperoxidase (cMPO) but negativity for CD34 and HLA-DR. Molecular analysis was negative for the canonical PML::RARA fusion but identified a rare TBC1D15::RAB21 fusion, alongside FLT3-internal tandem duplication (ITD) and NPM1 mutations. The stark contrast between the APL-like morphology and the molecular findings created a significant diagnostic pitfall, posing a risk for therapeutic misdirection. The patient achieved sustained remission following risk-adapted AML chemotherapy and allogeneic hematopoietic stem cell transplantation (allo-HSCT). This case underscores three critical points in pediatric AML: (1) the essential role of integrated molecular profiling in resolving morphologic ambiguities to prevent misclassification; (2) the complex prognostic impact of FLT3-ITD/NPM1 co-mutations in childhood AML; and (3) the potential therapeutic efficacy of allo-HSCT for rare fusion-driven subtypes.